Research of estimated human resources methods - O. S. Suvalov; T. V. Suvalova (Вестник университета)
The purpose of the study is to analyse the methods for evaluating personnel in hiring. The essence and relevance of evaluation methods, the reliability of the results and the frequency of use of evaluation methods in Russian recruitment companies have been considered in the article. Classical methods have been highlighted, the most popular, time-consuming, and demanded evaluation technologies have been noted. The attention is focused on the advantages of the competency model (interview on competencies), an example of the competency model of a personnel manager has been given. The effectiveness of using structured interviews to evaluate employees has been noticed. The relevance of identifying the degree of development of the "digital adaptability" competency, which allows the employee to navigate in the context of large-scale digitalization, has been substantiated, indicators of this competency have been considered. The role and tasks of the interviewer have been described.